DEVELOPING THE SPEAKING SKILL AMONG ESL ELEMENTARY LEARNERS (Proceedings of International Educators Conference, 2024)
This article aims to investigate and propose effective strategies for the development of speaking skills among elementary ESL (English as a Second Language) students. Speaking is a crucial aspect of language learning, particularly for ESL learners, as it is essential for communication and interaction in the target language. The research will focus on identifying the challenges faced by ESL elementary students in developing their speaking skills and exploring innovative methods to overcome these challenges. By examining various pedagogical approaches, such as communicative language teaching and task-based learning, this study seeks to provide practical recommendations to teachers, educators, and stakeholders working with elementary ESL students.